HUBUNGAN PENGETAHUAN IBU HAMIL DENGAN SIKAP TERHADAP SCREENING HIV/AIDS DI PUSKESMAS LUBUK BAJA KOTA BATAM TAHUN 2017 - Sita, Pipit Maria; Aryaneta, Yenni (Universitas Batam, 2017)
HIV / AIDS can be transmitted from Pregnant Mother to Children she carries. To Reduce the rate of said transmission, the government held free HIV / AIDS screening program for Pregnant Women at health centers. The purpose of this research is to know whether there is a relation between knowledge of pregnant woman with attitude toward HIV / AIDS screening at Lubuk Baja Health Center, Batam city, year 2017. This research is analytical descriptive research with a total sampling of 53 respondent from pregnant mothers who visit the health center in July. The data analysis method used is chi-square test at significance level of 95%. The research results based on the characteristics of respondents, there are 24 respondents who are knowledgeable and 34 respondents who have positive attitude toward the program. It can be concluded that there is a correlation between the knowledge of Pregnant Woman about HIV / AIDS screening with p-value = 0,002 and the attitude of pregnant woman toward HIV / AIDS screening with p-value = 0,001. It can be concluded that knowledge and good attitude of Pregnant Woman are very important in improving HIV / AIDS Screening. The writer suggests Pregnant women should participate in the Government Program, so the number of Mother-to-child HIV/ AIDS transmission can be reduced